2018
DOI: 10.1093/brain/awy077
|View full text |Cite
|
Sign up to set email alerts
|

Mutant LRRK2 mediates peripheral and central immune responses leading to neurodegeneration in vivo

Abstract: Missense mutations in the leucine rich repeat kinase 2 (LRRK2) gene result in late-onset Parkinson's disease. The incomplete penetrance of LRRK2 mutations in humans and LRRK2 murine models of Parkinson's disease suggests that the disease may result from a complex interplay of genetic predispositions and persistent exogenous insults. Since neuroinflammation is commonly associated with the pathogenesis of Parkinson's disease, we examine a potential role of mutant LRRK2 in regulation of the immune response and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
135
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 123 publications
(176 reference statements)
8
135
2
1
Order By: Relevance
“…For example, a recent investigation found that mice overexpressing mutant human LRRK2 (either R1441G or G2019S) exhibit increased dopamine neuron loss and neuroinflammation in response to systemic endotoxin challenge. 30 This study concluded that LRRK2 mediated the link between peripheral inflammation and neuroinflammation by augmenting peripheral production of CNS-modulating cytokines. If supported by future research, this finding could also partly explicate the association between PD and Crohn's disease.…”
Section: Microglia: More Than Macrophagesmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, a recent investigation found that mice overexpressing mutant human LRRK2 (either R1441G or G2019S) exhibit increased dopamine neuron loss and neuroinflammation in response to systemic endotoxin challenge. 30 This study concluded that LRRK2 mediated the link between peripheral inflammation and neuroinflammation by augmenting peripheral production of CNS-modulating cytokines. If supported by future research, this finding could also partly explicate the association between PD and Crohn's disease.…”
Section: Microglia: More Than Macrophagesmentioning
confidence: 87%
“…The successful work on microglial TREM2 in AD suggests that it may be important to reconsider the functions of classic PD‐associated genes—such as leucine‐rich repeat kinase 2 ( LRRK2 ), PTEN‐induced kinase 1 ( PINK1 ), and PRKN (Parkin)—and how their mutation or loss could impact microglial biology. For example, a recent investigation found that mice overexpressing mutant human LRRK2 (either R1441G or G2019S) exhibit increased dopamine neuron loss and neuroinflammation in response to systemic endotoxin challenge . This study concluded that LRRK2 mediated the link between peripheral inflammation and neuroinflammation by augmenting peripheral production of CNS‐modulating cytokines.…”
Section: Microglia: More Than Macrophagesmentioning
confidence: 99%
“…Experimental models also support this connection, whereby IFN-γ has been linked to selective, progressive, DA neurodegeneration in rodents 11,14,15 . More recent studies also point towards the interaction between PDrelated genes and IFN-γ induced DA neuronal loss 16 . The study by Kozina et al shows that human pathogenic mutations in the leucine rich repeat kinase 2 (LRRK2) gene, the most common genetic cause of familial and sporadic PD 17 , synergizes with lipopolysaccharide (LPS)-induced inflammation to potentiate DA neurodegeneration through IFN-γ-mediated immune responses 16 .…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies also point towards the interaction between PDrelated genes and IFN-γ induced DA neuronal loss 16 . The study by Kozina et al shows that human pathogenic mutations in the leucine rich repeat kinase 2 (LRRK2) gene, the most common genetic cause of familial and sporadic PD 17 , synergizes with lipopolysaccharide (LPS)-induced inflammation to potentiate DA neurodegeneration through IFN-γ-mediated immune responses 16 . Interestingly, LRRK2 is an IFN-γ target gene 18,19 and its expression is increased in immune cells upon IFN-γ stimulation and exposure to pathogens 18,20,21,22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, innate immune functions were demonstrated for several genes causatively-linked to familial forms of PD or ALS. These comprise C9ORF72 (21)(22)(23), LRRK2 (Leucine-rich repeat kinase 2) (24)(25)(26)(27), GRN (Granulin Precursor) (28,29) as well as PRKN and PINK1 (30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%